Dinamika Politik Ketatanegaraan Indonesia pada Masa Demokrasi Parlementer (1950-1959) - Fajri, Pujangga Candrawijayaning (IAIN Metro, 2025)
He declared the Declaration of Independence of August 17, 1945, as the opening gateway for Indonesia to organize its affairs independently, freely, and independently. Although Indonesia is already able to manage its own affairs, it does not mean that it will eliminate the potential conflict. Evidently, between 1950 and 1959, a chain of conflicts continued, while at that time it was known as a fairly democratic time when freedom of opinion was restricted and elections were held for the first time. Starting from what is meant, the aim of the research is to provide a thorough and comprehensive understanding of the political dynamics of Indonesian statehood in parliamentary democracy. The results of this research show that the political dynamics of statehood that occurred in the parliamentary democracies are colored by a variety of things, from the internal conflict of the Muslims because of the question of the division of posts in the cabinet to the constraint of the Constituante in formulating the state policy to the political intrigues played by Soekarno and the Army caused by the fact that they were unprofitable the whole time. Thus, the consequences of this have been a recession in the cabinet at a relatively rapid and unstable time for the national economy.